COPPER ABSORPTION STATUS OF AGRICULTURAL PLANT SPECIES AND THEIR PHYTOREMEDIATION POTENTIAL (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The aim of the present study was to determine the contents of copper in agricultural soils situated on Darazam recultivated tailing dump and in crops growing on these soils, to evaluate the risk level of studied plants for human health and to find out their phytoremediation potential. Results of the study show that in coriander (aerial part) and in garlic (aerial and underground parts) as well as in the leaves of horseradish (fresh mass) the exceeding of maximum permissible concentration of copper content was observed. The lowest contents of copper were registered in the beans of common bean as well as in the berries of red currant and raspberry therefore these plants may be used as foodstuff. Maize has the greatest phytoremediation potential from all studied plants so it is reasonable to use this species for the reclamation of the area under the study.
Keywords: Zangezur Copper and Molybdenum Combine, agricultural plants, copper accumulation, health risks, phytoremediation potential